Forgotten Topological and Wiener Indices of Prime Ideal Sum Graph of Z57;’ - Sözen, Esra Öztürk; Eryaşar, Elif; Abdiolu, Cihat (Current Organic Synthesis, 2024)
Background: Chemical graph theory is a sub-branch of mathematical chemistry, assuming each atom of a molecule is a vertex and each bond between atoms as an edge. Objective: Owing to this theory, it is possible to avoid the difficulties of chemical analysis because many of the chemical properties of molecules can be determined and analyzed via topological indices. Due to these parameters, it is possible to determine the physicochemical properties, biological activities, environmental behaviours and spectral properties of molecules. Nowadays, studies on the zero divisor graph of Zn via topological indices is a trending field in spectral graph theory. Methods: For a commutative ring R with identity, the prime ideal sum graph of R is a graph whose vertices are nonzero proper ideals of R and two distinctvertices I and J are adjacent if and only if I+J is a prime ideal of R . Results: In this study the forgotten topological index and Wiener index of the prime ideal sum graph of Zn are calculated for n=pα ,pq, p2q, p2q2, pqr, p3q, p2qr, pqrs where p, q, r and s are distinct primes and a Sage math code is developed for designing graph and computing the indices. Conclusion: In the light of this study, it is possible to handle the other topological descriptors for computing and developing new algorithms for next studies and to study some spectrum and graph energies of certain finite rings with respect to PIS-graph easily.
Keywords: Wiener index